2019
DOI: 10.3390/toxins11010042
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity and Structural Properties of Novel Synthetic Analogues of the Protozoan Toxin Climacostol

Abstract: Climacostol (5-[(2Z)-non-2-en-1-yl]benzene-1,3-diol) is a resorcinol produced by the protozoan Climacostomum virens for defence against predators. It exerts a potent antimicrobial activity against bacterial and fungal pathogens, inhibits the growth of several human and rodent tumour cells, and is now available by chemical synthesis. In this study, we chemically synthesized two novel analogues of climacostol, namely, 2-methyl-5 [(2Z)-non-2-en-1-yl]benzene-1,3-diol (AN1) and 5-[(2Z)-non-2-en-1-yl]benzene-1,2,3-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 54 publications
5
21
0
Order By: Relevance
“…In particular, experiments performed on human tumor squamous carcinoma A431 cells, and human promyelocytic leukemia HL60 cells demonstrated that climacostol exerts its action by inhibiting cell growth and triggering a mitochondrion-dependent apoptotic program. Subsequent extensive in vitro screenings and in vivo experiments confirmed the previous observations [4,21,[29][30][31].…”
Section: Climacostol Reduces Tumor Progression Via P53-dependent Apopsupporting
confidence: 76%
See 4 more Smart Citations
“…In particular, experiments performed on human tumor squamous carcinoma A431 cells, and human promyelocytic leukemia HL60 cells demonstrated that climacostol exerts its action by inhibiting cell growth and triggering a mitochondrion-dependent apoptotic program. Subsequent extensive in vitro screenings and in vivo experiments confirmed the previous observations [4,21,[29][30][31].…”
Section: Climacostol Reduces Tumor Progression Via P53-dependent Apopsupporting
confidence: 76%
“…The pro-apoptotic features of AN1 and AN2 on immortalized cell lines of both tumor (B16-F10, GL261, SK-N-BE, and CT26) and nontumor (C 2 C 12 ) origin were analyzed and compared with that of climacostol. The results indicated that cell viability was negatively affected by the two analogues with a comparable strength (Table 1), and both AN1 and AN2 displayed similar or even lower potencies when compared to climacostol [31]. Furthermore, as in the case of various tumor cells exposed to climacostol [4,29,30], immunostaining techniques revealed that B16-F10 melanoma cells expressed high levels of active caspase 3 after AN1 and AN2 treatment ( Figure 6), thus demonstrating the activation of an apoptotic pathway induced by both analogues.…”
Section: Antitumour Activitymentioning
confidence: 95%
See 3 more Smart Citations